CDR 2019
DOI: 10.20517/cdr.2019.006
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of hepatocellular carcinoma and cholangiocarcinoma

Abstract: Primary liver cancers constitute the fourth most deadly group of cancers. Their poor prognosis is due in part to the pre-existence and/or development, often during treatment, of powerful mechanisms accounting for the poor response of cancer cells to antitumor drugs. These include both impaired gene expression and the appearance of spliced variants, polymorphisms and mutations, affecting the function of genes leading to the reduction in intracellular concentrations of active agents, changes in molecular targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 206 publications
(247 reference statements)
0
7
0
Order By: Relevance
“…Targeted drugs, in particular antiangiogenic drugs, are today approved for the treatment of hepatocellular carcinoma, in which, however, they are endowed with low efficacy. Alonso-Peña et al [ 27 ] reviewed molecular alterations (mainly, germline polymorphisms and somatic mutations) that have been suggested to confer drug resistance to liver cancers (i.e., hepatocellular carcinoma and cholangiocarcinoma). However, despite the availability of a relevant number of studies that report potential associations among polymorphisms/mutations in genes codifying transporters or detoxifying enzymes, changes in molecular targets, enhanced DNA repair mechanisms, altered balance between survival and apoptosis pathways, tumor microenvironment and epithelial-mesenchymal transition, and cytotoxic or targeted anticancer drug efficacy and/or toxicity, no solid data are currently available and further investigation is needed.…”
mentioning
confidence: 99%
“…Targeted drugs, in particular antiangiogenic drugs, are today approved for the treatment of hepatocellular carcinoma, in which, however, they are endowed with low efficacy. Alonso-Peña et al [ 27 ] reviewed molecular alterations (mainly, germline polymorphisms and somatic mutations) that have been suggested to confer drug resistance to liver cancers (i.e., hepatocellular carcinoma and cholangiocarcinoma). However, despite the availability of a relevant number of studies that report potential associations among polymorphisms/mutations in genes codifying transporters or detoxifying enzymes, changes in molecular targets, enhanced DNA repair mechanisms, altered balance between survival and apoptosis pathways, tumor microenvironment and epithelial-mesenchymal transition, and cytotoxic or targeted anticancer drug efficacy and/or toxicity, no solid data are currently available and further investigation is needed.…”
mentioning
confidence: 99%
“…After hepatocellular uptake, sorafenib was N-oxidized by CYP3A4, one of the drug-metabolizing enzymes, to the pharmacologically active sorafenib-N-oxide metabolites [ 51 , 52 ] . However, CYP3A4 was identified as poorly expressed in liver cancer [ 53 ] . Well-studied oncomiRs (e.g., miR 21, miR-142 and miR-27b) overexpressed in HCC, which could be transferred by tumor-derived microvesicles (TMVs), were proved to be negatively associated with CYP3A4 mRNA in human liver [ 54 ] , which might downregulate the expression of this main enzyme and thus could inhibit the active biotransformation of sorafenib drug.…”
Section: Sorafenib Drug and Resistancementioning
confidence: 99%
“…Moreover, this study has reported other OCT1 mutations including c.262delT (p.Cys88Alafs*16) (*: position of new termination site represented by position number following) and c.181delCGinsT (p.Arg61Serfs*10). Such SNPs and mutations were manifested in lower sorafenib uptake thus, poorer clinical outcomes [38].…”
Section: Slc Transportersmentioning
confidence: 99%